DARING LECTURE CULTURE: PREFERENCE OF ISLAMIC EDUCATION LEARNING AT COLLEGE DURING AND POST COVID-19 OUTBREAK - Nuraliah Ali; Adilham Adilham (POTENSIA: Jurnal Kependidikan Islam, 2020)
Concerning the pandemic COVID-19, which was designated as a national disaster, the Ministry of Education and Culture issued a policy that every unit of education should transform face-to-eye learning into distance learning. In the context of Islamic education in college, the policy forced all actors of Islamic education to change the culture or customs of learning into distance-learning or online. This qualitative descriptive research seeks to describe systematically, scientifically, and factual descriptions, challenges, and strategies of ICT optimization/ utilization on each component of the lecture as a learning solution during and after the COVID-19 pandemic. The data collection methods used in this study are document content with data analysis using latent content analysis. The challenges faced in building a culture of online lectures are unqualified infrastructure, different socio-economic factors, the unpreparedness of human resources (resistance to change, attitudes and confidence, minimal digital skills), and resource accessibility. Constructing the culture of online lectures on Islamic education needs to pay attention to several aspects such as expected outcomes, required financing, responsibilities, resource requirements, and evaluation.